2016
DOI: 10.1007/s11356-016-7876-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood and hair trace elements and minerals in children living in metal-polluted area near copper smelter in Karabash, Chelyabinsk region, Russia

Abstract: The primary aim of the study is assessment of hair and whole blood trace element and mineral levels in children living in a polluted area near a copper smelter (Karabash) and two control locations (Varna, Tomino) using inductively coupled plasma mass spectrometry. The obtained data indicates that both blood and hair As, Pb, and Fe levels in children living in Karabash significantly exceeded the control values. Whole blood levels of copper in children living in Varna exceeded that in Tomino (p = 0.155) and Kara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
0
9
0
4
Order By: Relevance
“…In contrast, higher Ni levels were found when our data are compared with those of other studies, excepting those reported by Xie et al [30] in Shaoguan Guangdong (China) and Evrenoglou et al [14] in Athens (Greece). In turn, Pb levels were higher than those found in hair of children living in some mining, volcanic, sub-urban and urban areas [14,26,34,36,47] but lower than values from children living near certain mining zones, as well as near to toxic waste disposal sites and cement plants [11,30,34,35,37]. The individual characteristics of the geographic areas where the children live would probably be the responsible of the observed variability in Ni and Pb levels among studies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, higher Ni levels were found when our data are compared with those of other studies, excepting those reported by Xie et al [30] in Shaoguan Guangdong (China) and Evrenoglou et al [14] in Athens (Greece). In turn, Pb levels were higher than those found in hair of children living in some mining, volcanic, sub-urban and urban areas [14,26,34,36,47] but lower than values from children living near certain mining zones, as well as near to toxic waste disposal sites and cement plants [11,30,34,35,37]. The individual characteristics of the geographic areas where the children live would probably be the responsible of the observed variability in Ni and Pb levels among studies.…”
Section: Discussionmentioning
confidence: 84%
“…The concentrations of trace elements in hair of schoolchildren were compared with those of recent studies found in the scientific literature ( Table 5). Most of these investigations are focused on areas with important industrial or mining activities or even in urban zones [11,14,26,30,[34][35][36][37]46,47]. The different results might be attributed to the differences among the respective geographical areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Производственная и повседневная деятельность человека связана с увеличением содержания ряда токсичных микроэлементов [1][2][3][4]. Одним из наиболее опасных микроэлементов является свинец, который поступает в организм человека в основном алиментарным, ингаляционным путём и через неповреждённую кожу [5].…”
Section: Introductionunclassified
“…Предполагается, что содержание свинца в тканях человека (волосы, ногти, кровь и т.д.) является показателем экологического состояния окружающей среды [2,3,[23][24][25], поэтому во многих работах приводятся данные об источниках поступления микроэлемента в аэрогеотические звенья [2,3]. Среди прочего биоматериала многие авторы [1,2,23,26] отмечают преимущество волос для анализа концентрации металлов в организме человека.…”
Section: Introductionunclassified